Assessment of User Satisfaction with Educational Management Information System in Southwestern Nigerian Universities - Oluwatoyin Ayanlade; Tinuade Oluwatosin Akinwole; Timothy Oyedepo Oyebisi (CV Sinergi Ilmu dan Publikasi, 2026)
User satisfaction is a significant factor in ensuring the effective implementation and long-term viability of Educational Management Information Systems (EMIS) in higher education. This study examines the level of satisfaction among EMIS users in selected Nigerian universities, with specific attention to service quality, information quality, system quality, outcome expectations, and organizational factors. A mixed-methods approach was adopted, combining questionnaire surveys and semi-structured interviews among EMIS officers from state ministries of education, ICT personnel, university administrators, and students across six universities in Southwestern Nigeria. Quantitatively, three hundred copies of the questionnaire were administered among the students and staff (technology users) of the selected educational institutions using the EMIS technology and also among EMIS officers at the ministry of education in each of the states of the zone. Quantitative data were analyzed using mean ratings, while qualitative interview responses were analyzed thematically to provide contextual insight into user experiences. The mean ratings indicated that users were extremely satisfied with all the examined variables. Although this study's emphasis is on user satisfaction rather than administrative efficiency, it concluded that strengthening information quality, improving technical support services, and enhancing institutional commitment are essential for enhancing user satisfaction for sustainable use of EMIS in Nigerian universities.